2003
DOI: 10.1002/jat.906
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of cholesterol oxidation products to Caco‐2 and HepG2 cells: modulatory effects of α‐ and γ‐tocopherol

Abstract: Cholesterol can be oxidized to form a variety of cholesterol oxidation products also known as oxysterols. The aims of the present study were to compare the cytotoxic effects of four oxysterols, namely 25-hydroxycholesterol (25-OHC), 7beta-hydroxycholesterol (7beta-OHC), cholesterol-5beta,6beta-epoxide (beta-epox) and cholesterol-5alpha,6alpha-epoxide (alpha-epox), in two human cell culture models. Further, the ability of 10 and 100 micro m alpha- and gamma-tocopherol (alpha-TOC and gamma-TOC, respectively) to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 37 publications
2
23
0
Order By: Relevance
“…Studies from O'Sullivan and colleagues [24] have shown that 25-hydroxycholesterol, a-epoxy, b-epoxy or 7b-OH added individually to undifferentiated CaCo-2 cells determined a reduction in cell viability. The cytotoxicity exerted on undifferentiated CaCo-2 cells by 24 h treatment was assessed by the neutral red uptake assay and showed IC50 values with increasing concentrations of b-epoxy and 7b-OH (0e50 mM) [24].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Studies from O'Sullivan and colleagues [24] have shown that 25-hydroxycholesterol, a-epoxy, b-epoxy or 7b-OH added individually to undifferentiated CaCo-2 cells determined a reduction in cell viability. The cytotoxicity exerted on undifferentiated CaCo-2 cells by 24 h treatment was assessed by the neutral red uptake assay and showed IC50 values with increasing concentrations of b-epoxy and 7b-OH (0e50 mM) [24].…”
Section: Discussionmentioning
confidence: 97%
“…Studies from O'Sullivan and colleagues [24] have shown that 25-hydroxycholesterol, a-epoxy, b-epoxy or 7b-OH added individually to undifferentiated CaCo-2 cells determined a reduction in cell viability. The cytotoxicity exerted on undifferentiated CaCo-2 cells by 24 h treatment was assessed by the neutral red uptake assay and showed IC50 values with increasing concentrations of b-epoxy and 7b-OH (0e50 mM) [24]. Similar results were obtained in Caco-2 cells treated with 30 mM 7b-OH that inhibited cell growth by 50% at 32 h incubation and induced apoptosis, but in this case caspase-3 activity remained within control range during the whole observation time (72 h) [25].…”
Section: Discussionmentioning
confidence: 97%
“…Different types of oxysterols may influence cell signaling in various ways. 25-Hydroxycholesterol or 7-beta-hydroxycholesterol have been found cytotoxic for Caco-2 human colon carcinoma cell line [78], whereas lower concentrations of 25-hydroxycholesterol associated with IL-1beta induced production of inflammatory IL-8 in the same cells [6]. On the other hand, a mixture of oxysterols, obtained by cholesterol heating, that mimics the concentration of these compounds in cooked foods, increased the activation of liver X receptors (LXRs), which are important regulators of cholesterol catabolism and lipid metabolism, thus negatively influencing inflammatory cell response [85,120].…”
Section: Inflammatory Bowel Diseasesmentioning
confidence: 99%
“…Dietary lipids have an important pathophysiological impact on mucosa function: they influence membrane fluidity, which may alter cell signaling from the receptor system, immune response, inflammatory reactions and cell death [70,78]. A large body of evidence from epidemiological studies indicates that dietary lipids, such as polyunsaturated fatty acids (PUFAs) or cholesterol oxidation products, and intestinal microflora, are the main responsible for the production of oxidized species in the colon [78,115].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation